PET/CT imaging evidence of FUS‐mediated (18)F‐FDG uptake changes in rat brain. Issue 3 (12th February 2013) - Kim, Hyungmin; Park, Mi‐Ae; Wang, Shuyan; Chiu, Alan; Fischer, Krisztina; Yoo, Seung‐Schik
Abstract : Purpose: : Transcranial focused ultrasound (FUS) delivers highly focused acoustic energy to a small region of the brain in a noninvasive manner. Recent studies have revealed that FUS, which is administered either in pulsed or continuous waves, can elicit or suppress neural tissue excitability. This neuromodulatory property of FUS has been demonstrated via direct motion detection, electrophysiological recordings, functional magnetic resonance imaging (fMRI), confocal imaging, and microdialysis sampling of neurotransmitters. This study presents new evidence of local increase in glucose metabolism induced by FUS to the rat brain using FDG (18‐fludeoxyglucose) positron emission tomography (PET). Methods: : Sprague–Dawley rats underwent sonication to a unilateral hemispheric area of the brain prior to PET scan. The pulsed sonication (350 kHz, tone burst duration of 0.5 ms, pulse repetition frequency of 1 kHz, and duration of 300 ms) was applied in 2 s intervals for 40 min immediately after the FDG injection via tail vein. Subsequently, the PET was acquired in dynamic list‐mode to image FDG activity for an hour, and reconstructed into a single volume representing standardized uptake value (SUV). The raw SUV as well as its asymmetry index (AI) were measured from five different volume‐of‐interests (VOIs) of the brain for both hemispheres, and compared between sonicated and unsonicated groups. Results: : Statistically significant hemispheric changes in SUV were observed only at the center of sonication focus within the FUS group [paired t ‐test; t (7) = 3.57, p < 0.05]. There were no significant hemispheric differences in SUV within the control group in any of the VOIs. A statistically significant elevation in AI ( t ‐test; t (7) = 3.40, p < 0.05) was observed at the center of sonication focus (7.9 ± 2.5%, the deviations are in standard error) among the FUS group when compared to the control group (−0.8 ± 1.2%). Conclusions: : Spatially distinct increases in the glucose metabolic activity in the rat brain is present only at the center of sonication focus, suggesting localized functional neuromodulation mediated by the sonication.